A bacterial engineered glycoprotein as a novel antigen for diagnosis of bovine brucellosis. - Ciocchini, Andres Eduardo (2014)
Brucellosis is a highly contagious zoonosis that affects livestock and human beings. Laboratory diagnosis of bovine brucellosis mainly relies on serological diagnosis using serum and/or milk samples. Although there are several serological tests with different diagnostic performance and capacity to differentiate vaccinated from infected animals, there is still no standardized reference antigen for the disease. Here we validate the first recombinant glycoprotein antigen, an N-formylperosamine O-polysaccharide-protein conjugate (OAg-AcrA), for diagnosis of bovine brucellosis. This antigen can be produced in homogeneous batches without the need of culturing pathogenic brucellae; all characteristics that make it appropriate for standardization. An indirect immunoassay based on the detection of anti O-polysaccharide IgG antibodies in bovine samples was developed coupling OAg-AcrA to magnetic beads or ELISA plates. As a proof of concept and to validate the antigen, we analyzed serum, whole blood and milk samples obtained from non-infected, experimentally infected and vaccinated animals included in a vaccination/infection trial performed in our laboratory as well as more than 1000 serum and milk samples obtained from naturally infected and S19-vaccinated animals from Argentina. Our results demonstrate that OAg-AcrA-based assays are highly accurate for diagnosis of bovine brucellosis, even in vaccinated herds, using different types of samples and in different platforms. We propose this novel recombinant glycoprotein as an antigen suitable for the development of new standard immunological tests for screening and confirmatory diagnosis of bovine brucellosis in regions or countries with brucellosis-control programs.